Proton Stress Adaptation in Acidophilic Sulfate-Reducing Bacteria: Insights from Acididesulfobacillus Acetoxydans for Acid Mine Drainage Bioremediation - Egas, Reinier A.; Bale, Nicole J.; Koenen, Michel; Villanueva, Laura; Sousa, Diana Z.; Welte, Cornelia U.; Sánchez Andrea, Irene (American Chemical Society, 2026)
Acid mine drainage (AMD) waters are a global environmental threat due to their extremely low pH (<3) and high metal loads. Acidophilic sulfate-reducing bacteria (aSRB) can mitigate AMD by reducing sulfate to sulfide, a proton-consuming process that also precipitates metals as metal sulfides. Although sulfate reduction has been observed in AMD waters, most characterized aSRB are only moderately acidophilic. Here, we examined the pH tolerance and proton stress adaptation of the complete organic acid-oxidizing aSRB Acididesulfobacillus acetoxydans. Continuous chemostat cultivations were operated across a pH gradient, reaching steady states from pH 5.0 (optimum) to pH 2.9. In subsequent batch incubations, biomass from a pH 2.9 chemostat remained metabolically active at pH 2.5. Transcriptomic profiles remained remarkably stable across conditions, except for the upregulation of the K+-transporting ATPase (kdpABC) at lower pH, suggesting an increased reliance on the chemiosmotic gradient to impede proton influx. Lipid analysis revealed increased core lipid saturation, midchain methylation, and a shift in priming precursors from leucine to valine at low pH, indicating reduced membrane permeability and more energy-efficient biosynthetic pathways. Together, these adaptations likely reduce proton entry, explaining how aSRB adapt to AMD-like acidity and unlock the pH bottleneck for AMD bioremediation and metal recovery.
Keywords: 33 Ciencias Tecnológicas::3308 Ingeniería y tecnología del medio ambiente; ODS 7 - Energía asequible y no contaminante; ODS 15 - Vida de ecosistemas terrestres; acid stress; biosulfidogenesis; acidophiles; membrane remodeling; stress physiology